Soils & Fertilizers for Master Gardeners: Glossary of Soil and Fertilizer Terms - Shawna Loper; Amy L. Shober (EDIS)
Revised! SL277, a 4-page illustrated fact sheet by Shawna Loper and Amy L. Shober, contains the definitions of important soil and fertilizer terms used throughout the Soils and Fertilizers for Master Gardeners EDIS series. Published by the UF Department of Soil and Water Science, January 2009.